Family farming in the Near East and North Africa - Ray Bush (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
The United Nations International Year of Family Farming 2014 came at an important time for the region of the Near East and North Africa (NENA). This is because the political turmoil and uprisings that have structured politics and social policy in the region since 2010 (and as we will also see, from before this year too) demanded 'bread, freedom, social justice' (Aish, horreya, 'adala igtema'yyia). This slogan of protesters was heard in varied forms across the region. While most attention focused on urban rebellions in Tunisia, Egypt and Libya, where Western military intervention accelerated the removal from power of Muammar al-Gaddafi and the subsequent continued chaos, rural dissent and protest was also present across the region. Protests by small farmers across NENA had been very evident since the food price hikes of 2008 that had intensified rural malnutrition, poverty and inequality (Bush 2010). But the causes of protest had been long in the making and can be traced back to the onset of economic liberalisation in the mid-1980s, if not earlier. NENA is the world's largest food importer, relying on world markets for more than 50 per cent of its food. Price rises, particularly for wheat and rice, have given a stronger rationale to the strategic importance of boosting local production. The need to reduce the impact of the vagaries of volatile international markets for grain is - rhetorically at least - central to all countries in the region. Yet the strategy to reduce that dependence is shaped by intense local and international political pressures. The largely non-food-producing countries of the Gulf Cooperation Council (GCC) have intensified their search for land to purchase outside their national boundaries, while others, such as Egypt, have suggested the need to reinvigorate historical practices of land reclamation. All countries in the region are intent on increasing incentives to agribusiness investors. [...]
Keywords: 330; family farming; Near East; North Africa